Computer and Internet Information Skills for Sport - Sachs, M.
Computers, as information resources, have had a tremendous immeasurable impact on the conduct of scholarly research since around 1970 and the internet is just the latest development in this chain of innovations. For scholarly research, the bibliographic databases that started to appear in the early 1970's are arguably more important than the internet because they provide a gateway to collections of subject specific academic research articles from the significant journals and other information resources in the subject field(s) covered by each database. Some of the literature is from peer reviewed journals while other articles are culled from the trade journals and other literature sources in the discipline in which the database is rooted. Many databases also tend to be eclectic, drawing literature from subject disciplines that are neighbors to the field of coverage. Hence, for example, ERIC, a United States Government sponsored database that indexes and abstracts education periodicals and unpublished documents culls relevant articles from fields as diverse as communications, psychology, recreation, sociology and human resources along with the core coverage of the education journals and sources. On the other hand some databases, like Social Work Abstracts, stay much more strictly within the confines of their subject field's publications. Databases do have the characteristic that they are very predictable in their coverage. They index a specific group of periodicals, either selectively or from cover to cover. They cover a specific time range. Generally they do not cover even superb and highly relevant articles from journals not in their coverage list of periodicals. This is one reason for searching interdisciplinary topics in several relevant databases. That is to get a wider range of relevant citations, that come from a variety of viewpoints on the search topic.